Expert opinion on challenges in the diagnosis and treatment of OCD in India - Porandla, Kishan; Nagpal, Rajesh; Garg, Sanjay (International Journal of Research in Medical Sciences, 2024)
Obsessive-compulsive disorder (OCD) is considered as a significant cause of disability worldwide, ranking among the top 10 causes. The diagnosis of OCD is often delayed due to the reluctance of patients to share their symptoms. OCD is also associated with the presence of other comorbid psychological conditions like anxiety, depression, and schizophrenia among others, which adds to the challenge of accurate diagnosis. Delayed diagnosis and the presence of comorbid conditions have a poor prognosis. Hence, an increased awareness about identifying symptoms of OCD among doctors and the general public is important. Even though clinical practice guidelines outline the management for OCD, challenges in appropriate management exist. This review elaborates the challenges associated with the diagnosis and management of OCD in India and presents insights from experts which can help doctors in early diagnosis and appropriate management of this debilitating condition.